Microclima e qualidade de forragens em sistema silvipastoril agroecológico em função do tempo de repouso do pastejo e sombreamento - Militão, Érica Rui (2017)
The objective of this work was to evaluate the different levels of shading in the agroecological silvopastoral system and its influence on the microclimatic and qualitative aspects of the pasture. The experiment was carried out at the Paranaense Reference Center in Agroecology (CPRA), in the city of Pinhais/PR, from December 2015 to July 2016 and were used, composed by silvopastoral system with different tree species arranged in simple lines with pasture. The microclimatic data records were performed one day per month in three different time bands: from 8 am to 10 am, from 12 am to 2 pm and from 4 pm to 6 pm. In each picket, three collecting positions were defined as bands, within which three levels of visual shading were determined (under the tree canopy, intermediate and full sun), the microclimatic variables analyzed were: illuminance (lux), air temperature (°C), relative humidity (%), wind speed (m s- 1), measured at 20 cm from the soil and soil surface temperature (°C), measured with a laser sight directed to the surface layer. The fodder collections were carried out in the months of December 2015 to April 2016 and June, July and September of 2016. Within each picket, nine forage samples were collected, referring to the bands and levels of shading, previously described, and cut close to the soil. The samples were weighed and separated into grasses, legumes and spontaneous, then fractionated in leaves, stems and senescent material for the determination of the botanical components. For the bromatological evaluations the leaf and stem components were united in the same sample in order to determine the dry matter, crude protein, neutral detergent fiber and acid detergent fiber. The microclimate results showed interaction between hours and points for illuminance and soil surface temperature, generally for the two variables obtained lower values under the canopy of the trees; The greatest differences were found in the time zone from 12 am to 2 pm, between the collection point under the treetops and in full sun. The air temperature and the relative humidity of the air obtained differences between the hours with lower values of air temperature and humidity of the greater air, both in the range of 8am to 10am. Wind speed was highest in the 12 am range at 2 pm. The results obtained for grazing show, in general, that the grasses showed changes in responses to the shade, with leaf proportions, leaf/stem ratio, crude protein and dry matter higher at the collection point under the tree canopy.